Assessment of the Activity of Tigecycline against Gram-Positive and Gram-Negative Organisms Collected from Italy between 2012 and 2014, as Part of the Tigecycline Evaluation and Surveillance Trial (T.E.S.T.) - Stefania Stefani; Michael J. Dowzicky (MDPI AG, 2016)
As part of the Tigecycline Evaluation and Surveillance Trial (T.E.S.T) we report the in vitro activity of tigecycline and its comparators against Gram-negative and Gram-positive organisms collected from Italian centers between 2012 and 2014. Minimum inhibitory concentrations were determined according to the broth microdilution methodology of the Clinical and Laboratory Standards Institute, and antimicrobial resistance was determined using the European Committee on Antimicrobial Susceptibility Testing interpretive criteria. Among the Enterobacteriaceae, 31% of Escherichia coli isolates, 22% of Klebsiella pneumoniae, and 1% of Klebsiella oxytoca were extended-spectrum β-lactamase producers (ESBLs). Resistance rates among ESBL-K. pneumoniae and ESBL-E. coli to meropenem were 24% and <1%, respectively. Thirty-seven percent of K. pneumoniae were multidrug resistant (MDR) strains. Resistance rates among isolates of Acinetobacter baumannii to amikacin, levofloxacin and meropenem were between 84% and 94%. Eighty percent of A. baumannii isolates were MDR strains. Methicillin-resistant Staphylococcus aureus (MRSA) accounted for 38% of S. aureus isolates. No isolates of MRSA were resistant to linezolid, tigecycline or vancomycin. Antimicrobial resistance remains a problem in Italy with increasing numbers of MDR organisms. Despite high levels, MRSA rates appear to be stabilising. Tigecycline retains its in vitro activity against the majority of organisms, including those with multidrug resistance.